Like Beads on a String : Culture History of the Seminole Indians in North Peninsular Florida. - Weisman, Brent Richards (University of Alabama Press, 2010)
Florida's Seminole Indians are exerting an ever increasing influence on crucial issues in state politics, economy, and law. From a position of near obscurity less than a century ago, these Native Americans have staged a remarkable comeback to take an active hand in shaping Florida society, present and future. Anthropologists have long been fascinated with the Seminoles and have often remarked upon their ability to adapt to new circumstances while preserving the core features of their traditional culture. Early observers of the Seminoles also commented on the dynamic tension that existed for.